2008
DOI: 10.1038/nature06993
|View full text |Cite
|
Sign up to set email alerts
|

The role of the orbitofrontal cortex in the pursuit of happiness and more specific rewards

Abstract: Cues that reliably predict rewards trigger the thoughts and emotions normally evoked by those rewards. Humans and other animals will work, often quite hard, for these cues. This is termed conditioned reinforcement. The ability to use conditioned reinforcers to guide our behaviour is normally beneficial; however, it can go awry. For example, corporate icons, such as McDonald's Golden Arches, influence consumer behaviour in powerful and sometimes surprising ways 1 , and drug-associated cues trigger relapse to dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
143
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(161 citation statements)
references
References 29 publications
(30 reference statements)
17
143
1
Order By: Relevance
“…The OFC is critically involved on assigning and updating reward values, encoding a wide range of other variables indispensable for decision-making, including expected outcomes (Schoenbaum et al, 1998), effort associated to each option (Kennerley et al, 2009;Roesch and Olson, 2005), confidence in the decision (Kepecs et al, 2008) and the probability of win (Kennerley et al, 2009). Interestingly, rodent lesion studies have highlighted that the OFC encodes specific information about the outcome rather than its general affective value (Burke et al, 2008). Additionally, we had previously shown that chronic stress biased behavior from goal-directed to habit based choices, which was mediated by a shift from an atrophied medial prefrontal loop to a hypertrophied orbitofrontal network (Dias-Ferreira et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The OFC is critically involved on assigning and updating reward values, encoding a wide range of other variables indispensable for decision-making, including expected outcomes (Schoenbaum et al, 1998), effort associated to each option (Kennerley et al, 2009;Roesch and Olson, 2005), confidence in the decision (Kepecs et al, 2008) and the probability of win (Kennerley et al, 2009). Interestingly, rodent lesion studies have highlighted that the OFC encodes specific information about the outcome rather than its general affective value (Burke et al, 2008). Additionally, we had previously shown that chronic stress biased behavior from goal-directed to habit based choices, which was mediated by a shift from an atrophied medial prefrontal loop to a hypertrophied orbitofrontal network (Dias-Ferreira et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The OFC has been found to play an important role in reward processing (Burke et al, 2008;Assad, 2006, 2008). It is believed to form relative reward values to guide or top-down regulate human RD-oriented behaviors during reward processing (Rolls, 2000;Wallis, 2007).…”
Section: Reward Dependencementioning
confidence: 99%
“…Recent data suggest that the OFC is involved in signaling information about specific outcomes (9)(10)(11)(12)(13)(14). For instance, many OFC neurons signal both the value and the identity of the predicted outcome (12), and OFC lesions diminish the effects of outcome identity (but not general affective value) on conditioned behavior (13).…”
mentioning
confidence: 99%